Análise de uma proposta pedagógica para os anos iniciais do ensino fundamental : em foco a operação de multiplicação - Niemann, Flávia de Andrade (2013)
This research has investigated about theoretical methodological foundations to multiplication teaching in a pedagogical propose for early basic education in a private school,located in Passo Fundo/RS. This investigation involves quantitative approach and uses as methodology document research, because data collect and analisys were done by internal documents of planning (political-pedagogic project and learning goals) and student's educational materials (Activity notebook) from 1st to 5th grade, created by school's pedagogical staff. Data collect was made by reading and annotating organized in tables with the general description of each kind of document aim, the description of the approach for multiplication and the list of multiplicative structures' conceptual problem-situation in activity notebooks of each year. The information analisys was developed according to the Theory of Conceptual Models about formation of multiplication concept and contribution of Duval's studies about possibilities of use of semiotic representation's register transformation. The analisys shows that besides the resolution of different situations in multiplicative structures field is the basis of theorical methodological foundation of school's educational proposal for multiplication teaching, the concept of what is meant to this operation is the addition of equal tranch. The results of the research contribute for the reflection about the importance of theorical knoledge during the elaboration of new practises that prioritizes the appropriation of mathematics concepts in school enviroment